Regeneration of Mature Norway Spruce Stands: Early Effects of Selective Cutting and Clear Cutting on Seepage Water Quality and Soil Fertility - Wendelin Weis; Christian Huber; Axel Gattlein (The Scientific World Journal)
The cutting of trees influences element turnover in the forest ecosystem. The reduction of plant uptake, as well as an increased mineralization and nitrification due to higher soil temperature and soil moisture, can lead to considerable losses of nutrients from the main rooting zone. This may result in a reduced soil fertility and a decrease in drinking water quality due to high nitrate concentrations in the seepage water. In Bavaria (Germany) selective cutting is preferred to clear cutting when initiating the regeneration of Norway spruce stands with European beech. This paper summarizes the early effects of both forest management practices on soil fertility and seepage water quality for three different sites. Shown are the concentrations of nitrogen and base cations in the seepage water as well as the water and ion fluxes during the first year after tree cut. Nutrient inputs decreased on thinned plots and even more at clear-cuts. Nitrate concentrations in the seepage water are hardly affected by moderate thinning; however, on clear-cuts, the nitrate concentration increases significantly, and base cations are lost from the upper mineral soil. This effect is less obvious at sites where a dense ground vegetation, which is able to take up excess nitrogen, exists.